2019
DOI: 10.1126/science.aaw1773
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond x-ray diffraction reveals a liquid–liquid phase transition in phase-change materials

Abstract: In phase-change memory devices, a material is cycled between glassy and crystalline states. The highly temperature-dependent kinetics of its crystallization process enables application in memory technology, but the transition has not been resolved on an atomic scale. Using femtosecond x-ray diffraction and ab initio computer simulations, we determined the time-dependent pair-correlation function of phase-change materials throughout the melt-quenching and crystallization process. We found a liquid–liquid phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 79 publications
3
109
0
1
Order By: Relevance
“…The structural origin of these L‐L transitions was characterized by employing femtosecond x‐ray diffraction to observe the change in local atomic environment before crystallization occurred on the nanosecond time scale. It was found that the transition is predominantly caused by the onset of a Peierls distortion similar to that described in Figure . The occurrence of an L‐L transition in these materials therefore enables the fabrication of devices combining high speed with excellent data retention.…”
Section: Implications To Memory Technologymentioning
confidence: 69%
See 3 more Smart Citations
“…The structural origin of these L‐L transitions was characterized by employing femtosecond x‐ray diffraction to observe the change in local atomic environment before crystallization occurred on the nanosecond time scale. It was found that the transition is predominantly caused by the onset of a Peierls distortion similar to that described in Figure . The occurrence of an L‐L transition in these materials therefore enables the fabrication of devices combining high speed with excellent data retention.…”
Section: Implications To Memory Technologymentioning
confidence: 69%
“…The L‐L coexistence line ends with a critical point and is followed by the Widom line depicted as the blue dotted line. This behavior is representative of Si, ST2 water, and likely some PCMs . For the case of higher order L‐L transitions depicted in Figure B, the transition between the low‐density and high‐density phases is continuous and the boundary between the two phases is represented as a broader region with a finite width rather than a coexistence line.…”
Section: Liquid‐liquid Transitionsmentioning
confidence: 89%
See 2 more Smart Citations
“…As shown in Figure D, the 10‐year data retention shows a slightly better performance than that of the GST device (~82°C). This stability may have a relationship with suffocated diffusion or even a potential fragile‐to‐strong crossover in kinetics that has been recently proved to exist in many PCMs …”
Section: Phase‐change Materials For High‐speed Working Memory Applicamentioning
confidence: 99%